The Influence School Principal Leadership, Compensation, Discipline, On Teacher Performance - Vinalia Wati; Noni Setyorini; Heri Prabowo (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This research aims to determine the influence of school principal leadership, compensation, discipline on teacher performance (case study at MTs Nurul Huda Banyuputih, Batang Regency). This research used 32 respondents, the data collection process was carried out by distributing questionnaires using Google from to the teacher council at the school. This research uses quantitative methods. The data collection method uses a proportional random sampling technique with a questionnaire. This research uses multiple linear regression analysis methods with statistical testing tools. Measurements in this study used a Likert scale and data processing in this study used the IBM SPSS 25 tool. The results of this study show that there is an influence between the influence of the principal’s leadership, compensation and discipline on teacher performance. The regression results show that the regression coefficient (R2 ) obtained is 0.814. This means that 81.4% of teacher performance variables can be explained by leadership, compensation and discipline variables. Meanwhile, the remaining 18.6% is explained by other variables not included in this research model. (Shortcut: CTRL+ALT+A) Keywords: influence of principal leadership, compensation, discipline, teacher performance .